2007
DOI: 10.1080/08860220701260776
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alendronate, Risedronate, and Raloxifene on Renal Functions, Based on the Cockcroft and Gault Method, in Postmenopausal Women

Abstract: Background. Oral alendronate, risedronate, and raloxifene are effective treatment options in the management of postmenopausal osteoporosis. There is little previously reported about the renal safety profiles of these three agents in osteoporosis. We aimed to assess the risk of renal toxicity associated with oral alendronate, risedronate, and raloxifene in the treatment of osteoporosis, prospectively. Methods. One hundred and twentyseven patients with osteoporosis and osteopenia according to lumbar or femoral-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
0
18
0
2
Order By: Relevance
“…From the remaining 507 articles, 497 were excluded since they did not fulfill the selection criteria based on their titles and abstracts. After full-text checking of the rest of 10 RCTs [1521, 2527], 3 RCTs were excluded as their outcomes did not meet the inclusion criteria [2527]. Finally, 7 studies with usable information were included in our meta-analysis [1521] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…From the remaining 507 articles, 497 were excluded since they did not fulfill the selection criteria based on their titles and abstracts. After full-text checking of the rest of 10 RCTs [1521, 2527], 3 RCTs were excluded as their outcomes did not meet the inclusion criteria [2527]. Finally, 7 studies with usable information were included in our meta-analysis [1521] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The criterion for demonstrating equivalence is when both extremes of the confidence interval remain within the two vertical dotted lines. Data from Yanik et al [19] (one trial). Numerical values of mean difference −0.4 ml/min (95 % CI −10.3 to +9.5; 90 % CI −8.7 to +7.9).…”
Section: Abstract Osteoporosis · Bisphosphonates · Safety · Equivalencementioning
confidence: 98%
“…As regards renal adverse effects, while many studies have previously reported the occurrence of kidney dysfunction concomitant with the use of bisphosphonates, one limitation is that different outcome measures were used [19,20], and this makes it impossible to pool data from different trials and perform indirect comparisons. Further data are needed to clarify the renal safety profile of the overall class of bisphosphonates.…”
Section: Abstract Osteoporosis · Bisphosphonates · Safety · Equivalencementioning
confidence: 99%
See 2 more Smart Citations